The Impact of Working Capital Management on FirmValue: Evidence from a Frontier Market - Vijayakumaran, R.; Arachchi, A.N.H.; Perera, W. (Asian Journal of Finance & Accounting, 2017)
Corporate finance literature and finance practitioners have the notion that the efficient working capital management (WCM) affects firm value. This study investigates the value effect of working capital management, using a sample of 44 listed companies on the Colombo Stock Exchange (CSE) over the period 2011-2015. The CSE is currently recognized as a high growth frontier market (FM) in the world. The efficiency of WCM is measured using the Cash Conversion Cycle (CCC) and its components while firm value is measured by the Tobin Q ratio. The firm size, leverage and sales growth are used as the control variables. Using panel data regression methodology (the pooled OLS and fixed effects regressions), the study finds that CCC is inversely related to Tobin Q, suggesting that managers can create value for their shareholders by efficiently managing investment in working capital of their firms.
Keywords: capital management; firm value; panel data